2013
DOI: 10.1016/j.jacc.2013.03.086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Periprocedural Bleeding on Incidence of Contrast-Induced Acute Kidney Injury in Patients Treated With Percutaneous Coronary Intervention

Abstract: Periprocedural bleeding was significantly associated with CI-AKI, with CI-AKI incidence correlating with bleeding severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 23 publications
5
59
1
Order By: Relevance
“…25 More recently, the risk of AKI in PCI patients was identified to correlate with bleeding severity. 10 These findings are reproduced in our study; however, our study is unique in which we identified that this risk is valid even after adjustment for the utilization of blood transfusion. The relation between bleeding, blood transfusion, and AKI is complex and likely multifactorial.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…25 More recently, the risk of AKI in PCI patients was identified to correlate with bleeding severity. 10 These findings are reproduced in our study; however, our study is unique in which we identified that this risk is valid even after adjustment for the utilization of blood transfusion. The relation between bleeding, blood transfusion, and AKI is complex and likely multifactorial.…”
Section: Discussionsupporting
confidence: 75%
“…10 However, the relationship between anemia, bleeding, and transfusion and the risk of AKI has not been well studied. Further characterization of this relationship and definition of other risk factors might help broaden prophylactic strategies against post-PCI AKI.…”
mentioning
confidence: 99%
“…Recently, a strong association between bleeding and AKI was demonstrated in patients undergoing PCI. 16 Although we were able to corroborate this finding, the observed reduction in bleeding with TRI did not seem to mediate the reduction in AKI observed in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…16 Second, the risk of cholesterol embolization to the kidney may be minimized by avoiding catheterization of the descending aorta. It is possible that, by these mechanisms, the risk of AKI might be lower in patients undergoing TRI compared with transfemoral PCI (TFI).…”
mentioning
confidence: 99%
“…First, AKI is frequently complicated by altered immune function, increased propensity to infection, bleeding, and thrombosis. 25,26 Second, AKI can result in acute volume overload, acidemia, and hyperkalemia contributing to increased cardiac stress and risk of arrhythmias. 27 Third, crosstalk between the kidney and other organs involving inflammatory and proapoptotic pathways may result in multiorgan failure eventually causing death.…”
Section: Discussionmentioning
confidence: 99%